Anti-lipolytic action of AMP-activated protein kinase in rodent adipocytes - Daval, Marie; Diot-Dupuy, Francine; Bazin, Raymond; Hainault, Isabelle; Viollet, Benoît; Vaulont, Sophie; Hajduch, Eric; Ferré, Pascal; Foufelle, Fabienne (The Journal of biological chemistry, 2005)
Despite its importance in terms of energy homeostasis, the role of AMP-activated protein kinase in adipose tissue remains controversial. Initial studies have described an anti-lipolytic role for AMP-activated protein kinase, whereas more recent studies have suggested the converse. Thus we have addressed the role of AMP-activated protein kinase in adipose tissue by modulating AMP-activated protein kinase activity in primary rodent adipocytes using pharmacological activators or by adenoviral expression of dominant negative or constitutively active forms of the kinase. We then studied the effects of AMP-activated protein kinase activity modulation on lipolytic mechanisms. Finally, we analyzed the consequences of a genetic deletion of AMP-activated protein kinase in mouse adipocytes. AMP-activated protein kinase activity in adipocytes is represented mainly by the alpha(1) isoform and is induced by all of the stimuli that increase cAMP in adipocytes, including fasting. When AMP-activated protein kinase activity is increased by 5-aminoimidazole-4-carboxamide-riboside, phenformin, or by the expression of a constitutively active form, isoproterenol-induced lipolysis is strongly reduced. Conversely, when AMP-activated protein kinase activity is decreased either by a dominant negative form or in AMP-activated protein kinase alpha(1) knock-out mice, lipolysis is increased. We present data suggesting that AMP-activated protein kinase acts on hormone-sensitive lipase by blocking its translocation to the lipid droplet. We conclude that, in mature adipocytes, AMP-activated protein kinase activation has a clear anti-lipolytic effect.